FARMER GROUP EMPOWERMENT THROUGH THE FIELD SCHOOL OF INTEGRATED PLANT-MANAGEMENT (SL-PTT) PROGRAM IN BERU-BERU VILLAGE KALUKKU DISTRICT MAMUJU REGENCY - Lareken, muhammad S. Endro; Hidayat, Nur Azikin (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2024)
Developing the food crops sector is one of the key strategies to stimulate future economic growth. Besides being a major source of foreign exchange, this sector is the source of life for most of the Indonesian population. The increasing population has raised concerns over the state of "food insecurity" in the future. Therefore, to meet the food needs in the West Sulawesi province, the Department of Agriculture and Livestock initiated the Field-School of Integrated Plant Management (SL-PTT) program. This study is entitled "FARMER GROUP EMPOWERMENT THROUGH THE FIELD-SCHOOL OF INTEGRATED PLAN-MANAGEMENT (SL-PTT) PROGRAM IN BERU BERU VILLAGE KALUKKU DISTRICT MAMUJU REGENCY". The implementation of this program faces some issues such as the model applied in the program, the factors influencing the production and income, and the development pattern. This study aims to identify the implementation of the SL-PTT program in Beru-Beru Village including the inhibiting factors. This study was conducted in Beru-Beru Village, Kalukku District, Mamuju Regency. This study used a descriptive method with a qualitative approach. Data collection techniques covered observations, interviews, and documentation. Based on the results of the observation, the SL-PTT program has been successfully implemented. In practice, it manages to achieve the predetermined targets and objectives as well as involve farmers to participate in the improvement of agricultural yields. The inhibiting factors in the implementation of this program, include no response from the government for farmer groups who implement the SL-PTT program, lack of farmer group administrator effort to hold the counseling group meetings, different levels of soil fertility, different economic capabilities, unprepared use of agricultural technologies, and the limited budget allocation. Considering those challenges, the government of West Sulawesi province is expected to help increase the budget allocation for the implementation of this program, recruit the mentoring team based on technical competence aspects, and give insight to the community about the SL-PTT program.